Integrating Yoga with Psychotherapy: A Complementary Treatment for Anxiety and Depression - Forfylow, Andrea L. (Canadian Journal of Counselling and Psychotherapy, 2011)
This article addresses the empirical research on yoga as an effective, complementary, clinical intervention for anxiety and depression based on an examination of studies published from 2003 to 2010. There is a discussion of study findings and research limitations and suggestions for researchers and future research. Yoga appears to be an effective clinical intervention for anxiety and depression. However, more rigorous research needs to be completed to further support using yoga in mental health treatment planning. This article concludes with practical suggestions and implications for mental health professionals interested in using yoga.